Analisis Efisiensi Koperasi dan Faktor yang Mempengaruhinya di Kabupaten Banyumas - Arif Andri Wibowo; Muhammad Farid Alfarisy; Bambang Bambang (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The aim of the study is to analyze the level of cooperative efficiency in Banyumas Regency. The method used to achieve that goal is to use a quantitative approach. Quantitative approach is carried out through Data Envelopment Analysis (DEA). Dea is a methodology used to evaluate the efficiency of a decision-making unit responsible for using a number of inputs to obtain a targeted output. Our result shows that most of cooperative are not efficient. Factors affecting the efficiency are varies across coopertative.